Validity and reliability of the Malay version of the PSC-12 scale among healthcare workers in Malaysia - Abu Bakar, Norhasliza; Bulgiba, Awang; Isahak, Marzuki (Public Library of Science, 2025)
The prime instrument used to measure Psychosocial Safety Climate (PSC) at the workplace is the PSC-12 scale questionnaire, which has been widely used by researchers worldwide. We set out to translate the PSC-12 scale into Malay and validate it among Malaysian healthcare workers, the first time this has ever been attempted. We carried out a cross-sectional study among 250 healthcare workers from 3 government health clinics and 15 identified clinical work units in a public hospital in the Klang Valley area, Malaysia. The English version of the PSC-12 scale was translated into the Malay language (Bahasa Malaysia) and back into English to check for content accuracy and validity. Psychometric properties of the questionnaire were assessed for internal consistency (Cronbach’s alpha coefficient), temporal stability for test-retest reliability (intra-class correlation) and construct validity (confirmatory factor analysis). The translated questionnaire had a persistently high content validity-index (CV-I) of 0.916. The hypothesised four-factor-structure model displayed high goodness of fit indices (RMSEA = 0.081, SRMR = 0.032, GFI = 0.919, AGFI = 0.869, CFI = 0.961, and TLI = 0.946), demonstrating good questionnaire construct validity. Each item subscale in the PSC-12 scale showed satisfactory internal consistency with Cronbach’s alpha (α) coefficient between 0.895 to 0.921. There was satisfactory temporal stability and test-retest reliability with ICC (2,1) for scores of 0.954 (total item score), 0.897 (Domain 1 score), 0.910 (Domain 2 score), 0.807 (Domain 3 score) and 0.806 (Domain 4 score) over the two-week interval. The Malay version of the PSC-12 scale is a valid and reliable instrument for use among healthcare workers in Malaysia as evidenced by its satisfactory psychometric measure and construct structure properties.